The Effect Of Realia On Students’ Ability In Writing Descriptive Text At Seventh Grade Of SMP Swasta Cinta Rakyat 3 Pematang Siantar - Citra Sani Sinaga; Yanti Kristina Sinaga; Novra Melisa P. Hutabarat (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research was entitled The Effect of Realia on Student’s Ability in Writing Descriptive Text at Seventh Grade of SMP Cinta Rakyat 3 Pematang Siantar. The purpose of this research to find out significant effect of Realia on student’s ability in writing descriptive text at seventh grade of SMP Cinta Rakyat 3 Pematang Siantar. This research used scoring rubric by Jacob in wigle 2002 which is included five aspects: Content, Organization, Vocabulary, Language use and Mechanism. The method used in this research was quantitative method. This research used quasi- experimental design. The population of this research was seventh grade students of SMP Cinta Rakyat 3 Pematang Siantar. The samples of this reseach was took two classes as the sample of this research consists of 64 students. There sample of this research were VII-C as the experimental class and VII-D as the control class. This research used purposive sampling technique. This research used instrument writing test to collected the data for pre- test and post-test. From the data and result finding of the calculation, the researcher found that the mean score in the experimental class pre-test and post-test were 32,46 and the mean score in the control class pre-test and post-test were 22,93. After calculated the data overall, the researcher found the t-test score is 5,069. Then, the researcher consulted with value on t-table used significance 5% and the value is 1,670. Therefore, the researcher found that t-test is higher than t-table (5,069> 1,670) and Alternative Hypothesis (Ha) was accepted while Null Hypothesis (Ho) was rejected. It can be concluded that using Realia as the media in teaching writing descriptive text at seventh grade of SMP Cinta Rakyat 3 Pematang Siantar is significant.